(3JOGhd GdChQGb GdeGdjI hGdbjO aj GdMSGH (B:s (3OQGSI bGfhfjI ebGQfI aj fXGe GdEjOGY hGdbjO GdeQcRj ddChQGb GdeGdjI (B/s - (3aVdi, gTGes ((3GdEScfOQjI(B: s (3OGQ GdLGeYI(B, s, 2005)
(3fXGe GdEjOGY hGdbjO GdeQcRj hTQhW GdJOGhd(B-(3GdEjOGY hGdbjO GdeQcRj hCKGQ GdJOGhds
Keywords: (3CKGQ GdJOGhds; (3GdChQGb GdeGdjIs; (3GdEjOGY GdeQcRjs; (3GdJOGhds; (3TQhW GdJOGhds